Thrombocytopenia during pregnancy - Boehlen, F. (Hämostaseologie, 2006)
Thrombocytopenia is observed in 6 to 15% of pregnant women at the end of pregnancy, and is usually moderate. Gestational thrombocytopenia (defined as a mild thrombocytopenia, occurring during the 3rd trimester with spontaneous resolution postpartum and no neonatal thrombocytopenia) is the most common cause of thrombocytopenia during pregnancy but a low platelet can also be associated with several diseases, either pregnancy specific or not, such as preeclampsia, HELLP syndrome, or idiopathic thrombocytopenic purpura (ITP). The differential diagnosis between ITP and gestational thrombocytopenia is clinically important with regard to the fetus, due to the risk of neonatal thrombocytopenia. However, this differential diagnosis is very difficult during pregnancy.Thrombocytopenia which need to be investigated are the following: thrombocytopenia known before pregnancy, thrombocytopenia occurring during the 1st and 2nd trimester, platelet count < 75 G/l in the 3rd trimester or thrombocytopenia in case of pregnancy with complications. Investigations have to be discussed in function of history and clinical examination, gestational age and severity of thrombocytopenia.No treatment is required in case of gestational thrombocytopenia. There are few data to distinguish management of ITP between pregnant and non-pregnant women but management is different because of the potential adverse effects of the treatment for the woman and/or the fetus, the requirement for a good hemostasis at delivery and the risk of neonatal hemorrhage. One important problem is that it is not possible to predict the risk of neonatal thrombocytopenia in babies born from women with ITP.
Keywords: Thrombocytopenia; pregnancy; idiopathic thrombocytopenic purpura; gestational thrombocytopenia